2020
DOI: 10.3390/biology9070166
|View full text |Cite
|
Sign up to set email alerts
|

Plasma CAF22 Levels as a Useful Predictor of Muscle Health in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Skeletal muscle dysfunction and reduced physical capacity are characteristic features of chronic obstructive pulmonary disease (COPD). However, the search for a reliable biomarker to assess muscle health in CODP remains elusive. We analyzed the course of hand-grip strength (HGS) and appendicular skeletal mass index (ASMI) in COPD in relation to spirometry decline and plasma extracellular heat shock protein-72 (eHSP72) and c-terminal fragment of agrin-22 (CAF22) levels. We evaluated male, 62–73 years old patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
(51 reference statements)
1
32
1
Order By: Relevance
“…Body mass index (BMI) was calculated as kg/m 2 . Appendicular skeletal muscle mass (ASM) and fat mass were calculated with the bioelectrical impedance analysis scale (RENPHO, Dubai, UAE) as described previously [ 24 ]. ASM was divided by body area to get the appendicular skeletal muscle mass index (ASMI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Body mass index (BMI) was calculated as kg/m 2 . Appendicular skeletal muscle mass (ASM) and fat mass were calculated with the bioelectrical impedance analysis scale (RENPHO, Dubai, UAE) as described previously [ 24 ]. ASM was divided by body area to get the appendicular skeletal muscle mass index (ASMI).…”
Section: Methodsmentioning
confidence: 99%
“…No other body movement was allowed during the procedure. Three attempts were performed with each hand with a 60-s rest between each attempt and the highest value was recorded for analysis, as described by us previously [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia and other catabolic conditions disrupt NMJ integrity via proteolytic cleavage of agrin into CAF22 that can be detected in circulation. We have previously shown that plasma CAF22 levels are increased in sarcopenia with pulmonary diseases 9 , 16 . Here, we confirm and extend these findings to sarcopenia with CHF.…”
Section: Discussionmentioning
confidence: 91%
“…Candidate biomarkers for sarcopenia were selected based on the relevant literature and our previous investigations in patients with normal and advanced phases of sarcopenia 9 , 10 , 16 . Among various candidates investigated, circulating levels of P3NP, CAF22, osteonectin, irisin, FABP3 and MIF were significantly different in the COPF and CHF subjects with advanced sarcopenia, when compared to age-matched healthy controls.…”
Section: Resultsmentioning
confidence: 99%